Gender Gaps in Sociopolitical Attitudes A Social Psychological Analysis. (article). - Eagly, Alice H.
This research examined the proposition that differential role occupancy by women and men fosters gender gaps in sociopolitical attitudes. Analyses of the General Social Survey (J. A. Davis & T. W. Smith, 1998) and a community sample showed that women, more than men, endorsed policies that are socially compassionate, traditionally moral , and supportive of equal for women and for gays and lesbians. To clarify the sources of these gaps, the research examined (a) similarities between gender gaps and gaps associated with other respondent attitudes such as race and parenthood , (b) interactions between respondent sex and other attributes, (c) the temporal patterning of gender gaps and (d) the mediation of attitudinal gender gaps by 3 ideological variables -commitment to equality, group-based dominance, and conservatism versus liberalism. -- (from the author).